Predictive Modeling of Microemulsion Phase Behaviour and Microstructure Characterisation in the 1-Phase Region - Rout, Deeleep K.; Goyal, Richa; Sinha, Ritesh; Nagarajan, Arun; Paul, Pintu (IntechOpen, 2012)
None